(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Nation branding is not the "holy grail" of economic development, but it can provide a distinct advantage when it is aligned with a well-defined economic strategy and supported by public policy. A nation brand is the sum of people’s perceptions of a country across the most important areas of national competence. This paper examines the value of the nation brand on a sample of 108 countries, using the Anholt Nation Brands Index and using the mathematical formula for calculating the surface of Anholt’s hexagon for each country individually. In this paper, parameters are taken from six areas of the nation hexagon, from the World Bank and the UNESCO database. The surface of the nation hexagon was calculated with mathematical tools and comparative analysis was done between nation brands. By using strategic nation branding models designed by other branding experts in combination with a proposed mathematical model that shows the advantages and disadvantages of the nation brand of each country (and within the country), their competitiveness on the global stage is expected to improve.